Web-based intervention to increase uptake of prevention of parent-to-child transmission (PPTCT) service - An experience from the state of West Bengal, India - Ganguly, Suman; Goswami, Dipendra Narayan; Chakraborty, Debjit (Eastern Journal of Medical Sciences, 2017)
Background: To track human immunodeficiency virus (HIV)-infected pregnant women in every step of prevention of parent-to-child transmission (PPTCT) needs a line listing approach and a software-based line listing approach seems to be the best possible way to successful follow-up and linking the HIV-positive pregnant women with care, support, treatment, and other services. Objective: The purpose of this study is to assess the utility of web-based PPTCT line list software and to increase the uptake of PPTCT services by HIV-infected pregnant women. Methodology: The “web-based PPTCT line list software” was designed as a tool for monitoring uptake of PPTCT services by each HIV-positive pregnant woman detected in West Bengal in every step of PPTCT program. In collaboration with state IT cell, a software was developed where information of all positive pregnant women could be computed and based on the computed information, it could generate automatic SMS alerts regarding upcoming events to the counselor of the respective Integrated Counseling and Testing Center, the counselor of antiretroviral treatment (ART) center, outreach workers, and HIV-infected pregnant women. Simultaneously, entire state database can be viewed by program supervisor to monitor the program and to devise new strategies as per need. Results: Before the introduction of this software in August 2015, 92.8% (181/195) of the HIV-infected pregnant women could be linked to ART center during April 2015-August 2016. However, after its introduction, 98.8% (250/253) of them could be linked to ART center during September 2015-March 2016. This increase was statistically significant. Conclusion: The replicable software-based initiative would help in strengthening PPTCT linkages which could ultimately reduce the chance of HIV transmission through vertical route and to decrease the morbidity and mortality of HIV-exposed children.